Dampak Pandemi COVID-19 terhadap Kinerja UMKM dan Strategi Bisnisnya: Studi Kasus UMKM Irrenuang Parepare di Indonesia - Andi Ayu Frihatni; Irmayanti Sudirman; Frengky Mandacan (Jurnal Akuntansi dan Pajak, 2022)
The purpose of this study is to demonstrate the impact of the COVID-19 pandemic on the level of performance of MSMEs in revenue and income and to reveal the business strategy conducted by MSMEs. This research is qualitative with phenomenological approach conducted at MSMEs of Irrenuang in Parepare, South Sulawesi. MSMEs of Irennuang is one of the businesses engaged in the culinary field. The results of this study revealed that the performance level of MSMEs in income before and during the pandemic was 27.7%. During the pandemic, MSMEs add their business products in the form of Abon Ikan and Amplang Bandeng and utilize social media in marketing their products.